PERCEPTION OF THE SOCIETY ABOUT OPENING LAND WITHOUT BURNING AND THE INCENTIVE TO PREVENTION AND CONTROL FOREST FIRES IN RIMBO PANJANG VILLAGE KAMPAR REGENCY - Dewi Sriyanti; Defri Yoza; Tuti Arlita (Fakultas Pertanian, Universitas Riau, 2017)
Forest fires is one of the main causes of deforestation that could interfere with the preservation of forests. In 2015, there was a major fire that occurred again in Riau Province, one of them is in the village of Rimbo Panjang Kampar regency. Opening land by burning has become society’s habbit. This happens because there was no other alternative of society foropening land so they keep using fire in any opening land. This study aims to identify the information about forest and land fires that occurred in the village of Rimbo Panjang Kampar Regency, society’s perception in opening land without burning in Rimbo Panjang village of Kampar Regency and identify opportunities for incentives to the societyforopening land without burning. The results show that the number of fires from 2011 to 2015 in the village of Rimbo Panjang were 42 hotspots. Land and forest fires occur mostly during the dry season. The condition of land consist of shrubs and peat cause flammable. Society’s perception aboutopening land without burning describes that the public agrees with the activities of opening land systems without burning (PLTB) because it was considered more advantageous for the environment. The society do not know about the opportunities the incentive because the society has less knowledge about it, but if incentives are conducted, the society expect to be facilitated in the form of the provision of heavy equipment.